1994
DOI: 10.1111/j.1651-2227.1994.tb18277.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonography in the detection of achilles tendon xanthomata in children with familial hypercholesterolaemia

Abstract: Patients with heterozygous familial hypercholesterolaemia (FH) are at high risk for the development of coronary artery disease. Achilles tendon xanthomata are often the first clinical manifestation of FH, but are seldom palpable earlier than during the third decade. Twenty-one FH children aged 3-18 years underwent high-frequency ultrasound examination of the achilles tendon. Hypoechoic infiltration of the normal tendon structure was demonstrated in 8 of 21 (38%) of the FH children. The findings were similar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…When measuring the calcaneal tendon of a child and values are higher than the normality intervals, it is possible that there are, for example, xanthomas in this tendon, and that the child presents familial hypercholesterolemia (2) . If that is the case, a treatment could be immediately started, avoiding future problems resulting from such condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When measuring the calcaneal tendon of a child and values are higher than the normality intervals, it is possible that there are, for example, xanthomas in this tendon, and that the child presents familial hypercholesterolemia (2) . If that is the case, a treatment could be immediately started, avoiding future problems resulting from such condition.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has found significantly thicker calcaneal tendons in children above 3 years of age with a history of familial hypercholesterolemia, than in those included in a control group (2) . According to the authors, the cause for such thickening was the abnormal development of fat deposits (xanthomas) in the respective tendon.…”
mentioning
confidence: 99%
“…Ultrasonography is the most widely used, cross‐sectional, imaging modality for the evaluation of ATX [9,27,45–48,51,52,55–58]. The sonographic appearance of the normal Achilles tendon is characterized by the presence of multiple parallel linear echoes that give a fibrillar appearance (Fig.…”
Section: Detection Of Achilles Tendon Xanthomas (Table 1)mentioning
confidence: 99%
“…Τέλος τα αποτελέσματα μελετών που επιχείρησαν να συσχετίσουν το φύλο με την παρουσία ΑΤΧ είναι αντικρουόμενα433,436 ,441 . Ένα ακόμα μειονέκτημα της CT είναι η έκθεση του ασθενή σε ακτινοβολία.Η υπερηχοτομογραφία είναι η πιο ευρέως χρησιμοποιούμενη απεικονιστική μέθοδος για την εκτίμηση των ΑΤΧ410,426,[443][444][445][446][447][448][449][450][451] 452 ,453 ,454 ,455 . Η υπερηχογραφική απεικόνιση ενός φυσιολογικού Αχίλλειου τένοντα περιλαμβάνει πολλαπλά παράλληλα επιμήκη υπερηχητικά κύματα που δίνουν μια ινώδη εμφάνιση (εικόνα 17).…”
unclassified
“…Η υπερηχογραφική απεικόνιση ενός φυσιολογικού Αχίλλειου τένοντα περιλαμβάνει πολλαπλά παράλληλα επιμήκη υπερηχητικά κύματα που δίνουν μια ινώδη εμφάνιση (εικόνα 17). Σύμφωνα με διάφορες μελέτες ασθενών με FH, μία προσθιοπίσθια διάμετρος του τένοντα > 5.8-7.1mm θεωρείται παθολογική411,446,453,456 . Ωστόσο μόνο σε μία από αυτές τις μελέτες υπήρχε γενετική επιβεβαίωση της FH και σε αυτή τη μελέτη τα 5.8mm θεωρήθηκαν ως ένα όριο που επιτρέπει τη διάκριση των ασθενών με FH410 .…”
unclassified